Background of the foster family in Colombia and similar figures implemented in Argentina and Mexico - Higuera-Rondón, Nilson; Silva-Guevara, María Alejandra (DIXI, 2024)
The conception of the family has changed as of the new constitutional and conventional paradigms. This has implied the recognition of new types of families, among them those that are generated as a result of the bonds of affection and solidarity among their members, and that go beyond biological or legal filiation. The members of this type of family can exercise their rights under the parameters of equality and in accordance with the role of fathers, mothers, sons and daughters that they exercise in their family environment. The filial bond generated as a product of upbringing and affection has been recognized from the adoption of criteria that, in the case of Colombia, has been called foster family, while in countries such as Argentina and Mexico, criteria such as socio-affectivity and consolidated social reality, respectively, have been adopted, which have great similarities with respect to their doctrinal development. In the present text, we will approach, through a comparative exercise, the development that has taken place on this subject in the three countries.